The Effect of Live Streaming and Interactive Content on Purchase Interest TikTok Shop - Sri Dewi Susilawati; Lis Tatin Hernidiatiatin (International Journal Labs, 2026)
This study aims to analyze the influence of live streaming on consumer buying interest in the TikTok Shop application. The problem behind this research is the increasingly massive use of live streaming features as a marketing strategy in social commerce, but its effectiveness in encouraging consumer buying interest still needs to be proven empirically. This study used a quantitative approach with a survey method. The study population was TikTok Shop users who had watched sales live streams, with sample determination using purposive sampling techniques. Data was collected through a questionnaire based on the Likert scale and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of the SmartPLS application. The results of the study show that live streaming has a positive and significant effect on consumer buying interest. This shows that real-time interaction, direct delivery of product information, and visual appeal in live streaming can increase consumer interest and desire to make purchases. Based on these findings, it can be concluded that live streaming is an effective digital marketing strategy in increasing consumer buying interest on TikTok Shop. Therefore, business actors are advised to optimize the quality of content and interaction in live streaming to improve sales performance.